2011
DOI: 10.1089/lap.2010.0003
|View full text |Cite
|
Sign up to set email alerts
|

Is the Routine Use of Drainage After Elective Laparoscopic Cholecystectomy Justified? A Randomized Trial

Abstract: Our results indicate that routine drainage of gallbladder bed after elective LC may not be justified. Drainage causes more postoperative pain, prolongs the operative time and hospital stay, increases the occurrence of fluid in the subhepatic space, and does not protect from other complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 14 publications
1
38
0
8
Order By: Relevance
“…In Piotr's series, infectious complications were observed in 10% of the patients who had drainage after splenectomy. The Authors reported a shorter hospital stay in patients without drainage (6), data which is confirmed also by other surgeons (29)(30)(31)(32). Accordingly, Cohn (13) found a ten-fold increased risk of infectious complications in the splenic fossa, an increased risk which was observed also by Cherise et al (14).…”
Section: Discussionmentioning
confidence: 52%
“…In Piotr's series, infectious complications were observed in 10% of the patients who had drainage after splenectomy. The Authors reported a shorter hospital stay in patients without drainage (6), data which is confirmed also by other surgeons (29)(30)(31)(32). Accordingly, Cohn (13) found a ten-fold increased risk of infectious complications in the splenic fossa, an increased risk which was observed also by Cherise et al (14).…”
Section: Discussionmentioning
confidence: 52%
“…The meta‐analysis shows no statistically significant differences in wound infection and in mortality rates depending on the use or not of the drain. The drain may be a bacterial entrance toward peritoneal cavity, but morbidity is not statistically increased if short‐term drains are used in LC, as shown by Picchio and Georgiou . With regard to mortality, the result is reasonably not significant because LC is a well‐standardized surgical procedure and the presence or absence of the drainage is not related to this very rare complication.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, seven studies [9][10][11][12][13][14][15] were included in the metaanalysis with a total of 1310 patients.…”
Section: Meta-analysismentioning
confidence: 99%
“…Drains have also been used to remove remnant infectious debris or fluid and to prevent the formation of an intra‐abdominal abscess. However, several investigators have reported that the drain itself could become a bacterial entrance into the peritoneal cavity, which could cause ascending infection and result in wound infection at the insertion site of the drain . In our study, one intra‐abdominal abscess and four wound infections were observed in the group with drainage.…”
Section: Discussionmentioning
confidence: 99%